Effects of the pairing energy on nuclear charge radii - Weber, Christine; Herfurth, Frank; Kluge, Heinz-Jürgen (The European physical journal. A, Hadrons and nuclei, 2005)
Atomic masses of various radionuclides around the Z = 82 shell closure were determined with the ISOLTRAP mass spectrometer. This particular mass region is characterized by strong nuclear structure effects, like, e.g., shape coexistence. In this contribution results derived from mass spectrometry and laser spectroscopy are examined for a possible correlation between mass values and nuclear charge radii.